Charles A. Lindbergh Spirit of St. Louis collection - Lindbergh, Charles A. (Charles Augustus), 1902-1974.; Lindbergh, Charles A. (Charles Augustus), 1902-1974.
Chiefly Burmese, Dutch, English, and Swedish editions of the Spirit of St. Louis (1953). Includes "Reader's Digest" condensations in the Stockholm, Oslo, and Danish editions of the "Reader's Digest," dated April and May 1954; Lindbergh's address on receiving the Daniel Guggenheim Medal; and biographical material.
Aviator and U.S. Air Force officer.
Collection material in English, with other languages.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aeronautics; Aeronautics -- Awards; Daniel Guggenheim Medal; Spirit of St. Louis (Airplane); Transatlantic flights; Aviators; Air Force officers